Outcome Comparison Between Insulin-Dependent and Non Insulin-Dependent Patients after Open Adult Cardiac Surgery - Kurniawaty, Juni; Setianto, Budi Yuli; Supomo, Supomo; Widyastuti, Yunita; Ancilla, Cornelia; Boom, Cindy Elfira (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2023)
Background: Insulin-dependent diabetic patients usually have poor glycemic control and higher risk of complications than non-insulin-dependent diabetic patients. However, the difference in clinical outcomes between these two groups of patients who underwent open cardiac surgery was not established. Therefore, this study compares the short-term outcome of insulin vs non-insulin-dependent diabetic patients after open cardiac surgery in a large-scale study.Methods: The study design was a retrospective cohort. All adults who underwent open cardiac surgery between January 1st 2016-December 31st 2020 in 4 tertiary hospitals in Indonesia were included in the study. From a total of 4.931 samples included in the study, 3.753 patients were non-diabetic (Group I) and 1.178 were diabetic (Group II). Group II was divided into subgroup IIA (930 non-insulin-dependent) and subgroup IIB (248 insulin-dependent). The main outcome was in-hospital mortality of open cardiac surgery patients.Result: In-hospital mortality between group I and II had no significant difference (6.8% vs 5.7%; p = 0.188), as well as IIA and IIB (5.6% vs 6%; p = 0.782). Multivariate analysis demonstrated that diabetes did not increase mortality of open cardiac surgery (OR 0.665; p = 0.021). In-hospital mortality of subgroup IIB was higher than subgroup IIA, but insulin therapy did not increase the risk of in-hospital mortality (OR 1.259; p = 0.464).Conclusion: Both insulin-dependent and non-insulin-dependent diabetes mellitus were not the predictors of poor short-term outcomes for open adult cardiac surgery patients.